2007
DOI: 10.1055/s-2006-924658
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Marathon and Half-Marathon Performances

Abstract: We examined age-related changes in endurance performance of marathon and half-marathon finishers. A total of 405 515 running times were separated into groups based on age, sex, and distance. After exclusion of repetitive running times, 300 757 runners were analyzed by ANOVA (factors: age, sex). For each age group (six decades, 20-79 years), mean running times for all finishers, as well as top-ten performers, were assessed. As expected, age and sex had significant influence on running times. Female running time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
143
8
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(175 citation statements)
references
References 19 publications
16
143
8
8
Order By: Relevance
“…Age-related declines in endurance and ultra-endurance performance have been well described in the literature for running [24,35,38,54,83,89,90,91] , cycling [92,93,94,95] , swimming [83,85] and more recently, for triathlon. [34,79,92,96,97,98] Endurance and ultra-endurance performance appears to be maintained until approximately 35-40 years of age, followed by modest decreases until 50 years of age and a progressive decrease in performance thereafter.…”
Section: Age-related Declines In Triathlon Performancementioning
confidence: 89%
“…Age-related declines in endurance and ultra-endurance performance have been well described in the literature for running [24,35,38,54,83,89,90,91] , cycling [92,93,94,95] , swimming [83,85] and more recently, for triathlon. [34,79,92,96,97,98] Endurance and ultra-endurance performance appears to be maintained until approximately 35-40 years of age, followed by modest decreases until 50 years of age and a progressive decrease in performance thereafter.…”
Section: Age-related Declines In Triathlon Performancementioning
confidence: 89%
“…In recent years, there has been an increased interest in investigating the effects of aging on endurance performance in runners (Jokl et al 2004;Leyk et al 2007Leyk et al , 2009; Lepers and Cattagni 2011;Seals 2003, 2008;Wright and Perricelli 2008). Over the last decade, the participation of master athletes (>40 years old) in these events has increased, especially in the longer running distances such as half-marathons (Leyk et al 2007(Leyk et al , 2009, marathons (Burfoot 2007;Jokl et al 2004;Lepers and Cattagni 2011;Leyk et al 2007Leyk et al , 2009) and ultra-marathons (Hoffman 2010;Hoffman and Wegelin 2009;Hoffman et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the participation of master athletes (>40 years old) in these events has increased, especially in the longer running distances such as half-marathons (Leyk et al 2007(Leyk et al , 2009, marathons (Burfoot 2007;Jokl et al 2004;Lepers and Cattagni 2011;Leyk et al 2007Leyk et al , 2009) and ultra-marathons (Hoffman 2010;Hoffman and Wegelin 2009;Hoffman et al 2010). A recent analysis of the participation trend at the 'New York City Marathon' from 1980Marathon' from to 2009 showed that over the three decades, the percent of finishers at the 'New York City Marathon' younger than 40 years decreased, while the percent of master finishers increased for both males and females (Lepers and Cattagni 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations